Biomechanics of Knee Joints after Anterior Cruciate Ligament Reconstruction - He, Chuan; He, Wu; Li, Yanlin; Wang, Fuke; Tong, Lu; Zhang, Zhengguang; Jia, Di; Wang, Guoliang; Zheng, Jiali; Chen, Guangchao (The Journal of Knee Surgery, 2018)
This study aimed to investigate the biomechanical properties of anterior cruciate ligament (ACL); tibial, femoral articular cartilage; and meniscus in knee joints receiving computer-aided or conventional ACL reconstruction. Three-dimensional (3D) knee joint finite element models were established for healthy volunteers (normal group) and patients receiving computer-aided surgery (CAS) or conventional (traditional surgery [TS]) ACL reconstruction. The stress and stress distribution on the ACL, tibial, femoral articular cartilage, and meniscus were examined after force was applied on the 3D knee joint finite element models. No significant differences were observed in the stress on ACL among normal group, CAS group, and TS group when a femoral backward force was loaded. However, when a vertical force of 350 N was loaded on the knee joints, TS group had significant higher stress on the articular cartilage and meniscus than the other two groups at any flexion angle of 0, 30, 60, and 90 degrees. However, no significant differences were observed between CAS group and normal group. In conclusion, computer-aided ACL reconstruction has advantages over conventional surgery approach in restoring the biomechanical properties of knee joints, thus reducing the risk of damage to the knee joint cartilage and meniscus after ACL reconstruction.
Keywords: finite element; anterior cruciate ligament; reconstruction; knee joint; computer aided